Anxiety Level Survey Before and After the Bina Darma University Athletes' Competition at Pomprov in Palembang - Ria Oktafia; Bayu Hardiyono; Selvi Atesya Kesumawati (UNIB Press, 2022)
Anxiety is a signal that alerts, warns of an imminent danger and allows a person to take action to overcome the threat. This study aims to determine the level of anxiety of Bina Darma University athletes before and after the POMPROV match in Palembang. The research sample consisted of 89 students (male and female) aged 18-20 years. This research instrument uses a questionnaire on the anxiety level of HARS (Hamilton Anxiety Rating Scale) which is used before and after the match. The data analysis technique uses the percentage formula. The results of the analysis show that the level of anxiety (anxiety) of POMPROV UBD athletes before competing is as follows; no anxiety 14.61%, mild anxiety 22.47%, moderate anxiety 40.45%, severe anxiety 22.47%, and severe anxiety 0%. While the results of the analysis of the level of anxiety after the game are as follows; no anxiety 26.97%, category of mild anxiety 48.31%, moderate anxiety 22.47%, severe anxiety 2.25% and very severe anxiety 0%. based on the analysis of the data obtained, it can be concluded that the level of anxiety of UBD athletes at POMPROV 2022 Palembang has a mild anxiety category.